Structural and Biological Properties of Rhamnogalacturonan-I-Enriched Pectin Isolated from Cardamine tangutorum and Cardamine macrophylla - Mei-Mei Qu Mo; Bo Li; Ding-Tao Wu; Jing Feng; Jing Wei; Yan Wan; Juan Li; Yuan Liu; Wen-Bing Li (Foods, 2025)
C. macrophylla and C. tangutorum, collectively known as Shigecai in Chinese, are consumed as special and nutritious vegetables by the Tibetan, Qiang, and Yi communities in China. However, due to the insufficient knowledge of their phytochemical compositions and health benefits, the industrial utilization of these species in the food sector remains limited. Although Shigecai leaves contain substantial pectic polysaccharides, their chemical structures and biological activities remain unknown, which ultimately restricts their industrial utilization. Thus, to address this gap, this study systematically analyzed the chemical characteristics and biological functions of rhamnogalacturonan-I (RG-I)- enriched pectin from C. tangutorum (CTHDP) and C. macrophylla (CMHDP) leaves. The results demonstrate that Shigecai leaves are promising sources of RG-I-enriched pectin, with yields of 57.63–65.21 mg/g dry weight. In addition, both CTHDP and CMHDP exhibited highly similar chemical and structural properties, dominated by RG-I and homogalacturonan (HG) pectin regions, with RG-I ratios of 60.14–63.33 mol%. Furthermore, both samples demonstrated notable antioxidant ability, antiglycation activity, prebiotic potency, and immunoregulatory effects, which were strongly linked to their bound polyphenol content, uronic acid content, and molecular weight. These findings support the industrial utilization of Shigecai and establish Shigecai-derived RG-I-enriched pectin as a promising functional food ingredient.